UJI VARlETAS UBI JALAR (Ipomoea hatatas L.) PADA BERBAGAI JENIS PUPUK ORGANIK ALAMI DAN PUPUK BUATAN (N, P DAN K) - -, Sumarwoto; Wirawati, Tutut; Frisanto, Rifan (MAPETA, 2008)
The goal of this research is to get information about variety of sweet potato which have the highest production level and kind of fertilizer which give higher production level than 3 other examined varieties. The research was conducted in rainy season year 2005/2006 in Nayan village, Maguwoharjo, Depok, Sleman, DIY, using 3 kinds of  sweet potatoes: Boko, Sari, and Kalasan and using 4 kinds of fertilizer: organic matter formed from chicken feces, compost, and green fertilizer, also using manufacturer fertilizer mixed from N (Urea), P (SP36), and K(KCl). The experiment used Experimental Block Design (EED) Faktorial with 3 replications, The observation was conducted to several parameters: the amount of branch, lenght of main branch, weight of crop, amount of tuber, weight of tuber, diameter and average lenght of saleable tuber, amount of  tuber produced per ha, and sugar content in the tuber. The result of this research was the variety of Boko gave better growth in the amount of branch (19.50) and the lenght of' main bronch (178.63 cm), also gave the highest tuber produced ha-1 (13.12 ton). Organic fertilizer (chicken feces) gave the best result with 10 ton ha-1 doses, for the entire important parameters crop growth and the yield product observed, whereas on the supporting parameters, they generally gave of the same.